Optic Neuritis in Pediatric Patients - Rahmawati, Atik; Fatmawati, Dina (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2021)
Optic neuritis denotes an inflammation of the optic nerve characterized by loss of vision progressing over a few hours to a few days. Based on the site involved, optic neuritis is classified as retrobulbar (2/3 cases), atypical, and typical optic neuritis. In some cases, pediatric patients with optic neuritis have atypical symptoms and signs and no comprehensive medical history leading to a challenging diagnosis. In this case series, we report cases of optic neuritis in pediatric patients at different ages and clinical features treated with methylprednisolone 1 mg/kg body weight and oral mecobalamin and respective management. With a poor initial vision at presentation, the patients recovered rapidly.Â  The diagno-sis of optic neuritis was based on anamnesis, ophthalmologic examination, and simple laboratory and physical examination. The administration of steroids at a dose of 1 mg/kg body weight followed by a taper of dose can improve vision loss.